Redefinition of the Parameters of Meaningful Mathematics Learning - Exequiel R. Gono Jr, Emilia P. Pacoy (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study employs an integrated research design with emphasis on quantitative design that determines the dimensions of meaningful learning experiences in Mathematics. There were primary data gathered in this study comprised the (a) data from the responses of the research participants from one on one interview, and (b) data coming from the responses in the survey questionnaires. The researcher used two types of instruments to gather relevant information in the realization of the research objectives. The first research instrument is intended to gather data from the responses of the research participants using in-depth interview. The second type of research instrument is the output of the quantitative part which is the survey questionnaire. The researcher used two data analysis for qualitative data and quantitative data. The use of these analyses was based on the assumption of the fluidity of the responses of the research participants and the statistical assumption of the statistical tool. The researchers used the Colaizzi’s Seven Stage Process (1978) in analyzing the responses of the participants and Exploratory Factor Analysis in exploring and determine the factors of meaningful learning experiences. Based on the results and findings of the study, the dimensions of meaningful mathematical learning in mathematics comprises of six distinct factors which are theintentional meaningful learning, cooperative meaningful learning, real-life setting, derivative subsumption, advance organizer and educative processes